Las categorias del desarrollo economico y la investigacion en ciencias sociales - González Casanova, Pablo, 1922- (Instituto de Investigaciones Sociales, 1967)
Study of political aspects of social research in capitalist and socialist countries - covers problems of international cooperation in the fields of social sciences, and explores the influence of social theory and political theory in the evaluation of economic development and social change. References.